The study of reactions of 7-substituted 8-hydrazino-3-methylxanthine with β-dicarbonyl compounds - N. I. Romanenko; M. V. Nazarenko; D. G. Ivanchenko; O. O. Pakhomova; T. A. Sharapova (Zaporozhye State Medical University, 2015)
The problem of searching biologically active compounds amidst xanthine derivatives is a crucial one and is an issue for long-term investigation. The aim of this paper was to study reactions of 7-substituted 8-hydrazino-3methylxanthine with acetylacetone and acetoacetic ether. Methods and results. Reaction of 7-substituted 8-hydrazinoxanthines together with acetylacetone is performed by way of forming the respective 7-substituted 8-(3,4-dimethylpyrazole-1-yl)-3-methylxanthines. Interaction of hydrazinoxanthines with the excess of acetoacetic ether proceeds with the formation of 8-(3,4-dimethyl-6-oxopyrano[2,3-s]pyrazol-1-yl)xanthines. Conclusion. The investigated spectral characteristics of synthesized compounds indicate of relevance of IR-, NMR- and mass spectra to the proposed structure -(3,4-dimethyl-6-oxopyrano[2,3-s]pyrazol-1-yl)xanthines and 7-substituted 8-(3,4-dimethylpyrazole-1-yl)-3-methylxanthine.